The exhaustive Leviathan: The crisis of the State in Mexico - Acosta Silva, Adrián (1997)
At the end of the "prolonged" 20th century, the national States in Latin America present multiform faces, derived from more or less intense processes of reform of their profiles, powers and capacities. In such circumstances, the turn of the century seems to bring with it a new long-range transitional cycle that begins with the post-adjustment policies of the late 1980s and continues with the state reform processes of the 1990s.